Satellite Networks for Key Management - Koltuksuz, Ahmet; Koltuksuz, Ahmet (Institute of Electrical and Electronics Engineers Inc., 2007)
The cryptographic key management center is the place where all the cryptographical protocols and related keys are in action. Traditionally the key management centers operate on the ground. However; with the satellites, it is possible to conceive a space based key management center. This paper underlines the pros and cons of having a satellite networks key management center.
3rd International Conference on Recent Advances in Space Technologies, RAST 2007; Istanbul; Turkey; 14 June 2007 through 16 June 2007
Keywords: Public key cryptography; Aerospace industry; Cryptography; Management; Satellites